A Unified Total Site Heat Integration targeting method for isothermal and non-isothermal utilities. (15th January 2017) - Tarighaleslami, Amir H.; Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R.W.; Liew, Peng Yen; Neale, James R.
Abstract: This paper presents a new unified Total Site Heat Integration (TSHI) targeting methodology that calculates improved TSHI targets for sites that requires isothermal (e.g. steam) and non-isothermal (e.g. hot water) utilities. The new method sums process level utility targets to form the basis of Total Site utility targets; whereas the conventional method uses Total Site Profiles based excess process heat deficits/surpluses to set Total Site targets. Using an improved targeting algorithm, the new method requires a utility to be supplied to and returned from each process at specified temperatures, which is critical when targeting non-isothermal utilities. Such a constraint is not inherent in the conventional method. The subtle changes in procedure from the conventional method means TSHI targets are generally lower but more realistic to achieve. Three industrial case studies representing a wide variety of processing industries, are targeted using the conventional and new TSHI methods, from which key learnings are found. In summary, the over-estimation of TSHI targets for the three case studies from using the conventional method compared to new method are 69% for a New Zealand Dairy Factory, 8% for the Södra Cell Värö Kraft Pulp Mill, and 12% for Petrochemical Complex. Highlights: A new Total Site Heat Integration Targeting method is developed and presented. Process level targeting in the new method constrains non-isothermal utility use. A dairy factory, a pulp and paper mill, and a petrochemical complex are targeted. Comparisons suggest the conventional method over-estimates Total Site Heat Integration. Targets from the new method are lower but more realistic to achieve.